Criticizeability of a Classical Critical Text - Nassif, Nassif Muhammad (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The current research criticizes a classical critical text that appeared in (The Book of Al- Aghani) with two supportive clues: it is reflection to (Musa’b Ibn Abdullah al-Zubeiri), in which it handles the poetry of (Umar Ibn Abi Rabiaa) and highlights his position among contemporaries and peers. This research describes (Musa’b’s) text: it discloses the style, analyses the constituents, interprets the critical terms and viewpoints, tends to pursue the implications through scrutinizing the proposed poetical coexistences, up towards conceptualizing the emerging critical insight-being a critical insight that represents a creative approach within the critical thinking of Arabs. This is due to that the fact that Musa’b’s legacy stands as the primordial classical critical Arabic text that encompasses the receptor’s viewpoint in the comprehensive intuitive experience. Nonetheless, it does not consider the influential impressionistic rules that had been concurrent at that age sufficient, neither finds it efficient to have one, two or three lines of verse to pinpoint its viewpoints, as had been the custom. Rather, it studies the wholesome of Omar’s literary production (Umar’s Anthology) being one single text in which he pours his expertise, thoughtfully penetrates its essence in an attempt to uncover the secrets distinguishability, excellence over its contemporary texts. Therefore, it stands as the first critical Arabic text that examines the (stylistic uniqueness) that characterizes an outstanding creative figure via the creator-receptor interaction over the domain of the text.